3D Printed Multiplexed Competitive Migration Assays with Spatially Programmable Release Sources. Issue 1 (5th December 2019) - Haring, Alexander P.; Thompson, Emily G.; Hernandez, Raymundo D.; Laheri, Sahil; Harrigan, Megan E.; Lear, Taylor; Sontheimer, Harald; Johnson, Blake N.
Abstract: Here, a 3D printed multiplexed competitive migration assay is reported for characterizing a chemotactic response in the presence of multiple spatially distributed chemoattractants. The utility of the assay is demonstrated by examining the chemotactic response of human glioblastoma cells to spatially opposing chemotactic gradients of epidermal growth factor (EGF) and bradykinin (BK). Competitive migration assays involving spatially opposing gradients of EGF and BK that are optimized in the absence of the second chemoattractant show that 46% more glioblastoma cells migrate toward EGF sources. The migration velocities of human glioblastoma cells toward EGF and BK sources are reduced by 7.6 ± 2.2% and 11.6 ± 6.3% relative to those found in the absence of the spatially opposing chemoattractant. This work provides new insight to the chemotactic response associated with glioblastoma‐vasculature interactions and a versatile, user‐friendly platform for characterizing the chemotactic response of cells in the presence of multiple spatially distributed chemoattractants. Abstract : A 3D printed migration assay for the analysis of a chemotactic response in the presence of spatially distributed sources of chemoattractants is presented. The assay enables multiplexed studies with on‐plate controls. The device has broad applications ranging from the analysis of competitive chemotactic responses associated with diseases and development of 3D printed constructs.